Obesity and Insulin Resistance Induce Early Development of Diastolic Dysfunction in Young Female Mice Fed a Western Diet - Manrique, Camila (Endocrinology, 2013)
Cardiovascular disease (CVD), including heart failure, constitutes the main source of morbidity and mortality in men and women with diabetes. Although healthy young women are protected against CVD, postmenopausal and diabetic women lose this CVD protection. Obesity, insulin resistance, and diabetes promote heart failure in females, and diastolic dysfunction is the earliest manifestation of this heart failure. To examine the mechanisms promoting diastolic dysfunction in insulin-resistant females, this investigation evaluated the impact of 8 weeks of a high-fructose/high-fat Western diet (WD) on insulin sensitivity and cardiac structure and function in young C57BL6/J female versus male mice. Insulin sensitivity was determined by hyperinsulinemic-euglycemic clamps and two-dimensional echocardiograms were used to evaluate cardiac function. Both males and females developed systemic insulin resistance after 8 weeks of a WD. However, only the females developed diastolic dysfunction. The diastolic dysfunction promoted by the WD was accompanied by increases in collagen 1, a marker of stiffness, increased oxidative stress, reduced insulin metabolic signaling, and increased mitochondria and cardiac microvascular alterations as determined by electron microscopy. Aldosterone (a promoter of cardiac stiffness) levels were higher in females compared with males but were not affected by the WD in either gender. These data suggest a predisposition toward developing early diastolic heart failure in females exposed to a WD. These data are consistent with the notion that higher aldosterone levels, in concert with insulin resistance, may promote myocardial stiffness and diastolic dysfunction in response to overnutrition in females.